TECHNOLOGY OPTIMIZATION OF β-CAROTENE PRODUCTION BY MEANS OF MATHEMATICAL DESIGN OF EXPERIMENTS - A. G. Kuregyan; E. F. Stepanova (Разработка и регистрация лекарственных средств, 2019)
This article presents the results of modeling and optimization of the process of producing carotenoids by the example of β-carotene. The complex quantitative estimation of five technological parameters influence on the exit of individual carotenoid is conducted by the method of the mathematical planning of experiment. The complex quantitative estimation of influence of five technological parameters is conducted on the exit of individual carotenoids the method of the mathematical planning of experiment. The goal is achieved by constructing a mathematical model based on regression equations of the first order. We prove the adequacy of the work produced mathematical models and optimization carried out the process of obtaining β-carotene by a steep ascent.